Developing a Technology-Integrated Picture and Picture Model Assisted by Enuma and Wordwall for Early Reading and Learning Interest - Atikaharni, Wulan; Wikanengsih, Wikanengsih; Hutajulu, Masta (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aims to develop and test the effectiveness of the Picture and Picture learning model assisted by the Enuma and Wordwall application and to assess the level of feasibility and practicality based on expert validation and user responses, and the effect of its application on students' learning interest in first grade elementary school. The research method used is Research and Development (R&D) with the Borg and Gall stages which include ten product development steps. The research subjects consisted of two first grade classes at SD IT Insan Kamil and Bina Insan Cendekia as the experimental and control classes with a pretest-posttest design. Data collection techniques included reading ability tests, learning interest questionnaires, observations, and interviews. Statistical analyses were determined based on normality testing results, with parametric tests applied to normally distributed data and nonparametric alternatives used otherwise. This approach ensured methodological rigor and strengthened the validity of the findings and N-Gain calculations. The findings of this study indicate that the developed learning model has been assessed as very feasible and practical through validation by experts and practitioners. The application of the Picture and Picture model assisted by Enuma and Wordwall can significantly improve students’ early reading ability, as reflected in the significant difference in posttest scores between groups, although the N-Gain improvement between classes was not statistically significant (Sig=0.216). Furthermore, students' learning interest also increased descriptively, reaching the moderate category. Thus, this learning model has proven effective as an innovative alternative for improving early literacy in elementary school students.